2021
DOI: 10.1002/gj.4294
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of b‐values in Indo‐Burma Ranges, northeast India: Implications to structural heterogeneities and style of faulting

Abstract: The spatial distribution of the b‐value has been determined using a homogeneous earthquake catalogue from 1964 to 2018 to examine the characteristics of structural heterogeneities and their bearing on the style of faulting in the Indo‐Burma region of Northeastern India. The study region is associated with an uneven distribution of structural heterogeneities and demonstrates the mixed type of faulting, nature where the majority of earthquakes resulted mainly by thrust and strike‐slip fault. Our critical analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Khan et al (2011) reported a variation in the b ‐value from 0.23 to 1.78 for entire northeast India. Likewise, Bora et al (2018) and (2021) reported the spatial disparity of the b ‐value for the IBR region from 0.70 to 1.50. In the present study, the low b ‐value of 0.84 is reported for the grid lying between 25°–27° N and 94°–96° E while the maximum b ‐value of 1.51 is reported for the grid lying between 23°–25° N and 96°–98° E.…”
Section: Resultsmentioning
confidence: 89%
“…Khan et al (2011) reported a variation in the b ‐value from 0.23 to 1.78 for entire northeast India. Likewise, Bora et al (2018) and (2021) reported the spatial disparity of the b ‐value for the IBR region from 0.70 to 1.50. In the present study, the low b ‐value of 0.84 is reported for the grid lying between 25°–27° N and 94°–96° E while the maximum b ‐value of 1.51 is reported for the grid lying between 23°–25° N and 96°–98° E.…”
Section: Resultsmentioning
confidence: 89%
“…In the paper by Bora, Borah, et al (2022), the spatial distribution of the b ‐value has been determined using a homogeneous earthquake catalogue from 1964 to 2018 to examine the characteristics of structural heterogeneities and their bearing on the style of faulting in the Indo–Burma region of North‐eastern India. A close comparison between b ‐values and different faulting styles reveals that the area containing a low b ‐value suggests stronger seismogenic zones, where an accumulation of strain energy leads to the genesis of seismicity by thrust faulting with slight slip component whilst Indo–Burma Ranges regions connected with b ‐values (0.5–0.9) demonstrate strike‐slip to the normal mode of faulting, indicating relatively weak seismogenic zones where tensional forces are prevalent.…”
Section: Research Outputs Of Special Issue‐ Partmentioning
confidence: 99%
“…This Special Issue‐ Part 2 is a continuation of earlier Special Issue‐ Part 1 published in vol. 57 (2), of Geological Journal , which contained 26 research articles (Ao & Satyanarayanan, 2022; Baral et al, 2022; Bhowmik et al, 2022; Bora, Borah, et al, 2022; Bora, Mukherjee, et al, 2022; Deb & Ray, 2022; Devi & Singh, 2022; Devrani et al, 2022; Doley et al, 2022; Gogoi et al, 2022; Gupta et al, 2022; Hazarika & Kayal, 2021; Imtisunep et al, 2022; Liu et al, 2022; Luirei et al, 2022; Lukram & Tandon, 2022; Bidyananda et al, 2022; Majumdar, Gogoi, & Ghatak, 2022; Majumdar, Gogoi, Ghatak, Saikia, et al, 2022; Mukherjee et al, 2022; Pebam et al, 2021; Rashid et al, 2022; Saikia et al, 2022; Singh and Kshetrimayum, 2021; Singh, Guruaribam, Singh et al, 2022; Singh, Singh, Singh, et al, 2022; Srivastava, 2021; Srivastava & Kichu, 2021). Figure 2 displays the area of study of 29 papers included in this Special Issue 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation